2018
DOI: 10.3389/fphys.2018.00737
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of miR-499 rs3746444 Polymorphism for Cancer Risk of Different Systems: Evidence From 65 Case-Control Studies

Abstract: MicroRNAs (miRNAs) are a class of endogenous, short and non-coding RNAs that may play important roles in the pathogenesis of tumor. The associations between microRNA-499 rs3746444 polymorphism and cancer risk in different systems remain inconclusive. This article is aimed to obtain more exact estimation of these relationships through a meta-analysis based on 52,456 individuals. We retrieved relevant and eligible studies from Pubmed and Embase database up to January 10, 2018. ORs and 95% CIs were used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 76 publications
(73 reference statements)
2
16
0
Order By: Relevance
“…Polymorphisms within microRNA genes may have an impact on an individual's susceptibility to cancer. The MIR499A rs3746444 polymorphism, for example, has been shown to be significantly associated with risk of cancer of the respiratory, digestive, urinary and gynecological systems 34 . Over the past decade, a growing number of studies have examined the association between MIR499A rs3746444 polymorphism and breast cancer susceptibility, but the results were inconsistent and often contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms within microRNA genes may have an impact on an individual's susceptibility to cancer. The MIR499A rs3746444 polymorphism, for example, has been shown to be significantly associated with risk of cancer of the respiratory, digestive, urinary and gynecological systems 34 . Over the past decade, a growing number of studies have examined the association between MIR499A rs3746444 polymorphism and breast cancer susceptibility, but the results were inconsistent and often contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammatory cytokines in cardiovascular disease is well established [116]. MiR-499 polymorphism (rs3746444) has also been reported to be associated with cancers [117] and autoimmune diseases [118].…”
Section: Mir-499 Rs3746444 A>gmentioning
confidence: 99%
“…Accumulating evidence suggests a vital role for heredity in determining potential risk for malignancy. Yang et al recently performed a meta-analysis and identified the relationship between miRNA-499 rs3746444 A>G variants and risk to overall cancer was significant involving 23,762 cases and 28,694 controls 18. In addition, this study reported that miRNA-499 rs3746444 A>G variants also have been implicated in the risk of digestive system cancer.…”
Section: Discussionmentioning
confidence: 76%
“…The miRNA-499 rs3746444 A>G polymorphism was also associated with overall survival and progression-free survival among cases of neoadjuvant chemotherapy 16. A meta-analysis indicated that miRNA-499 rs3746444 variants were risk factors for overall cancer development 17,18. However, the correlation of miRNA-499 rs3746444 A>G variants with the susceptibility of AEG remains unclear.…”
Section: Introductionmentioning
confidence: 99%